Lord, I want to be Whole The power of prayer and scripture in Emotional Healing - Omartian, Stormie (Nashville Thomas Nelson Publishers, 2001)
The author presents a comprehensive guide to biblical wholeness, and offers seven steps to building a positive relationship with God.
Keywords: Mental health -- Religious aspects -- Christianity. Christian women -- Religious life